2010
DOI: 10.1159/000322330
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factors NFAT and CREB Have Different Susceptibilities to the Reduced Ca<sup>2+</sup> Responses Caused by the Knock Down of Inositol Trisphosphate Receptor in HEK 293A Cells

Abstract: Background/Aims: The inositol 1,4,5-trisphosphate receptor (IP3R), a ligand-gated Ca2+ channel, plays an important role in the control of intracellular Ca2+. Three isoforms of IP3R have been identified and most cell types express different proportions of these isoforms. The purpose of this study was to investigate how IP3R signalling is involved in the activation of the Ca2+-sensitive transcription factors NFAT and CREB. Methods: Each IP3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Activation of endogenous histamine receptors in HeLa cells showed a 2-fold activation of NFAT in WT cells which is lost in TKO cells (Fig 1B). These observation are in line with published data showing loss of NFAT stimulation by B-cell receptor activation in DT40 TKO cells (2), and reduced NFAT activation in HEK293A cells after siRNA knockdown of type 2 IP3Rs (21). As a control to verify that NFAT was still responsive to Ca 2+ in TKO cells, we tested the effect of the Ca 2+ ionophore ionomycin.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Activation of endogenous histamine receptors in HeLa cells showed a 2-fold activation of NFAT in WT cells which is lost in TKO cells (Fig 1B). These observation are in line with published data showing loss of NFAT stimulation by B-cell receptor activation in DT40 TKO cells (2), and reduced NFAT activation in HEK293A cells after siRNA knockdown of type 2 IP3Rs (21). As a control to verify that NFAT was still responsive to Ca 2+ in TKO cells, we tested the effect of the Ca 2+ ionophore ionomycin.…”
Section: Resultssupporting
confidence: 92%
“…The different ionophore response in HeLa cells may be due to the lack of RCAN1 changes, but it should be noted that the regulation of CRTC2 is also different in HeLa cells since they lack an upstream kinase (LKB1) needed to maintain phosphorylation of CRTC2 (31). In a previously published study on HEK293A cells it was shown that optimal responses of CREB to Ca 2+ mobilizing hormone requires the addition of vasoactive intestinal peptide (VIP), a cAMP-elevating stimulus (21). Treatment with VIP alone or in combination with ionophore caused a very large activation of CREB in both cell lines which was not significantly different in the TKO cells (Fig 2A & B).…”
Section: Higher Basal Activity Altered Ca 2+ Sensitivity and Increase...mentioning
confidence: 99%
“…In contrast, CREB inhibition involves BK Ca -dependent hyperpolarization modulating [Ca 2+ ] i via LTCC channels [35], and this signal will therefore be significantly affected by the initial activation state of VSMCs, their basal [Ca 2+ ] i , and membrane potential, as well as the number of LTCC channels on the membrane. Interestingly, NFAT signalling has recently been shown to directly depend on Ca 2+ release from IP 3 Rs, whereas CREB was generally unaffected by IP 3 R knockdown in HEK cells [94]. This is in contrast to the VSMC data [41], but whether this is attributable to cell differences or whether the previously shown importance of IP 3 Rs for CREB activation is also indirect, similarly to RYRmediated signalling [59], remains unclear.…”
Section: Ca 2+ -Dependent Transcription Factors and Vsmc Functionmentioning
confidence: 83%
“…The mRNA expression of RMP was also examined in human normal cell lines including kidney QBI-293A cells 23, WI-38 cells of a diploid human cell culture line composed of fibroblasts from normal embryonic lung of female 24 and three normal hepatic cell lines of QSG-770125, HL-7702 26 and L02 27. Apparently, all 7 cancer cell lines expressed higher RMP mRNA level than that in 5 normal cell lines (Fig.…”
Section: Resultsmentioning
confidence: 97%